Effect of leaf nutrition with yeast and urea on growth and productivity of cucumber in greenhouses - ديوب عبير; نصر شيخ سليمان (Latakia University Journal -Biological Sciences Series, 2024)
This study was conducted during the spring season of 2021 in the village of Bsaisin, which is 3 km away from Jableh in Lattakia city, in order to study the effect of foliar feeding with urea compound and yeast suspension on the growth and productivity of cucumber plants within the greenhouse. Five treatments were used In the experiment: urea compound at a concentration of (200-300mg/l) and yeast suspension at a concentration of (4-6g/l) in addition to the control treatment in four replications for each treatment. With regard to growth Indicators, urea recorded 300 mg/l, the highest plant height and capacity (232.1 cm), the largest number of leaves (45.93 leaves), and the largest number of branches (10,400 branches), and thus It gave the largest leaf surface, which amounted to (18217 cm2). The results also showed that foliar spraying with urea 300 mg/l gave the largest number of fruits (81.94 fruits) and the largest average weight of the fruit (106.90 g), and resulted In the largest production (30.58 kg/m2).